Analisis Beban Kerja Dan Kompetensi Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum Penataan Ruang Kabupaten Tulungagung - Evi Rochmawati (Universitas Islam Kadiri, 2020)
The organization is a social unit that is consciously coordinated with a relatively identifiable boundary, works continuously to achieve goals, the success of the organization depends on the ability of employees to operate work units contained in the organization. If an organization is able to achieve its goals, it can be said that the organization is effective. This study aims: (1) To find out and analyze workload and competence simultaneously affect the performance of the Tulungagung Regency Spatial Planning Public Works Department. (2) To find out and analyze the workload partially affect the performance of the Tulungagung Regency Spatial Planning Public Works Department. (3) To find out and analyze competencies partially affect the performance of the Public Spatial Planning Department's staff in Tulungagung Regency. This study uses a quantitative analysis method, namely analysis of data that has been given a score in accordance with a predetermined measurement scale using statistical formulas. The analysis used is data in the form of numbers. While technical data analysis uses: (1) reliability test, (2) validity test, and (3) multiple linear regression analysis. The results showed that: (1) The effect of workload and competence influential simultaneously had a significant effect on the performance of the staff of the Public Spatial Planning Office of Tulungagung Regency. (2) The effect of workload partially has a significant effect on the performance of the Tulungagung Regency Spatial Planning Public Works Department. (3) The effect of work competence is partially influential which has a significant effect on the performance of the Tulungagung Regency Spatial Planning Public Works Department.